STUDI ETNOBOTANI HUTAN MANGROVE DI TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Sari, Dian Marta; Eka Putri, Irma Leilani; Rizki, Rizki (STKIP PGRI Sumbar, 2013)
ABSTRACT Ethnobotany is a study of benefit plants by the society to support life need. It has great benefit especially for the society who live around mangrove area. One of mangrove forest in West Sumatera is in Teluk Buo Kecamatan Bungus Teluk Kabung Padang city. It has many advantageous. It can be physical aspect, ecological aspect and economical aspect. The purpose of this study is to find the kinds of mangrove that was used by the people in Teluk Buo Keamatan Bungus Teluk Kabung Padang city. This research was conducted on June 2013. The method that as use is survey method through observation and directly selecting the sample in the field of the research, monitoring, collecting the note in the field. The sampling technique was using vertical and horizontal technique. Collecting of data by society with 33 respondent. The research meet 17 species mangrove plants benefit by society, 11 species benefit to medicine is Ardisia elliptica, Hibiscus tiliaceus, Melastoma candidum, Acanthus illicifolius, Bruguiera gymnorrhiza, Lumnitzera littorea, Pongamia pinnata, Scyphiphora hidrophyllaceae, Rhizophora apiculata, Ceriops tagal, and Cassia alata. 15 species mangrove plants to benefit another is Ardisia elliptica, Hibiscus tiliaceus, Melastoma candidum, Bruguiera gymnorrhiza, Lumnitzera littorea, Pongamia pinnata, Scyphiphora hidrophyllaceae, Rhizophora apiculata, Aegiceras corniculatum, Ficus microcarpa, Dolichandrone spathacea, Pandanus odoratissima, Nypa fruticans, Ceriops tagal and Sonneratia caseolaris.